Multiphoton-And SHG-Active Pyrimidine-Based Liquid Crystalline Thin Films Toward 3D Optical Data Storage - Nicolas, Prescillia; Minon, Celia; Abdallah, Stephania; Chen, Dong; Rizzi, Giorgia; de Coene, Yovan; Liu, Weizhen; Jeannin, Olivier; Verbiest, Thierry; Clays, Koen; Bellec, Nathalie; Bilgin-Eran, Belkis; et al. (WILEY-V C H VERLAG GMBH, 2025)
An original asymmetric achiral pyrimidine core molecule, with long carbon chains on one side and a coumarin fragment on the other, is designed. This advanced molecular structure enabled the spontaneous emergence of crystalline and liquid crystalline thin films with strong 2nd harmonic generation (SHG) without any corona polishing process or tedious deposition techniques. Moreover, pin-pointed multiphoton absorption in the liquid crystalline phase effectively switches off the SHG signal locally and permanently, underlining its interest in 3D data storage. This prototypical material, which can be fully addressed by NLO processes, multiphoton writing, and SHG reading, paves the way for the development of efficient flexible materials for 3D optical data storage. A liquid crystal phase of an original pyrimidine-based bent-core molecule allows for data storage by multiphoton absorption and readout by second harmonic generation (SHG) imaging, holding great promise for 3D data storage. image
Keywords: liquid crystal; non-linear optic; optical storage; pyrimidine; EXCITATION CROSS-SECTIONS; 2-PHOTON ABSORPTION; 2ND-HARMONIC GENERATION; PHOTOISOMERIZATION; PHOTOPHYSICS; COMPOSITE; STANDARDS; DYES; Materials Science; Optics